Analisis Faktor Demografi dan Faktor Berkaitan Kerja dalam Kecenderungan Meletak Jawatan - Jati Kasuma, Haji Ali (1999)
This study is try to examine the relationship between demographic and factor related to work with intention to leave among non-managerial clerical staff in banking sector. Researcher able to collect all the questionnaires from the respondent. Interview and electronic email also being use to get all the data. By using inferential method, results shows that nine of hypothesis made are significant and only demographic factor i.e marital status are not significant. Among nine of the independent variables, only three that is job pressure, income and management style are found to be more statistically significant.